2020
DOI: 10.1111/jam.14550
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and antimicrobial resistance of Enterococcus from the Upper Oconee Watershed, Georgia

Abstract: Aim It is well‐known that enterococci are abundant in the environment; however, the role of surface water as a reservoir of antimicrobial‐resistant enterococci remains largely undefined. In this study, surface water samples were collected over a 2‐year period from the Upper Oconee watershed, Athens, GA to examine enterococci and their antimicrobial resistance. Methods and Results Approximately 97% (445/458) of the samples were positive for enterococci and a total of 637 enterococci were isolated. The predomina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 48 publications
1
16
1
Order By: Relevance
“…In our previous study, most of the Enterococcus isolates from surface water were resistant to at least one antimicrobial drug with multiple resistant phenotypes identified in a total of 51 isolates [12]. For the current study, those isolates that were resistant to three or more antimicrobial classes were further tested to investigate the molecular mechanism of AR and the abundance and diversity of plasmids among enterococci from surface water.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In our previous study, most of the Enterococcus isolates from surface water were resistant to at least one antimicrobial drug with multiple resistant phenotypes identified in a total of 51 isolates [12]. For the current study, those isolates that were resistant to three or more antimicrobial classes were further tested to investigate the molecular mechanism of AR and the abundance and diversity of plasmids among enterococci from surface water.…”
Section: Discussionmentioning
confidence: 99%
“…pEF1071 is a member of rep 11 family, and enterocins 1071A and 1071B are known to be encoded on pEF1071 [45]. Since enterocins exhibit antimicrobial activity and the producer bearing the plasmid would have a survival advantage over other closely related species present in the same ecological niche [45], it is possible that the presence of pEF1071 enabled E. casseliflavus to be the most frequently identified species and also the most common species with MDR phenotypes found in the surface water [12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, research has gained momentum on the topic of studying AMR and MDR in nonclinical and opportunistic environmental bacteria [5][6][7][8][9][10]. Some of these more recent studies on environmental resistance have revealed the prevalence of AMR and MDR in bacteria in soil [11][12][13], water bodies and watersheds [14][15][16][17][18][19][20][21][22][23][24], oceans [25]; glaciers [26], and animals [27,28]. For example, D'Costa et al [11] found MDR in all 480 soil isolates they screened for the 21 major classes of antibiotics.…”
Section: Introductionmentioning
confidence: 99%